Efektivitas Penggunaan Media Ular Tangga dan VideoTerhadap Peningkatan Pengetahuan Kesehatan Reproduksi Anak Tunagrahita - Ike Pratiwi Ike Pratiwi; Nina Hidayatunikmah; Anik Latifah (LPPM STIKES Mataram, 2025)
Introduction:Reproductive health problems in adolescents in Indonesia are still high caused by lack of knowledge. Not everyone has the same opportunity to get a proper education. One group that often has difficulty in getting an education is children with intellectual disabilities. One way to increase the knowledge of children with intellectual disabilities is by snake and ladder media and videos Objective: The purpose of this study was to see the effectiveness of snakes and ladders and video media on the level of knowledge of reproductive health of children with intellectual disabilities in SLB Negeri Samarinda.. Methods:This study is quantitative using one group pre-test and post-test design. The sample in this study amounted to 32 students in both groups of ladder 16 media and 16 video media taken using the Total Sampling method. The data was analyzed using an independent sample t test. Results:The results of the independent sample t test show that snake and ladder media and video media know the value of Sig. (2-tailed) of 0.000 or p < 0.05 so it can be concluded that the effectiveness of the use of snakes and ladders and videos both increase the knowledge of children with disabilities on reproductive health in SLB Negeri Samarinda. Conclusion: Thus, both educators and health workers are expected to be able to convey reproductive health information using effective media so that students understand more about it. Keywords: Health education, Islamic boarding schools, scabies prevention behavior